Remediating Tasik Sri Aman, Puchong to a high-functioning biodiversity landscape - Zulkifli, Maryam Adila (2018)
The main aim of this dissertation is to study on how to improve the water quality within Tasik Sri Aman, Puchong vicinity where it aspires to remediate Tasik Sri Aman, Puchong into a constructed wetland with multiple ecosystem services through implementing design strategies through these objectives; proposing a wetland to capture and filter stormwater or wastewater treatment through phytoremediation, protect and recover the native and as to provide a public space for recreational use and aesthetics experience, as well as foster urban development at Tasik Sri Aman, Puchong. In order to comply these objectives, a case study was conducted at Tasik Sri Aman, Puchong that was facing wetland degradation and disintegrating water quality. The challenge faced translates why it is vital to improve the water quality as to improve the community’s wellbeing and as well as encouraging high functioning biodiversity landscape to Tasik Sri Aman, Puchong. The dissertation concludes that Tasik Sri Aman has the potential to be developed into a high functioning and diverse in habitat for the community where it can be valued through the improvement of the water quality.